(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to determine the impact that marketing quality management has through its dimensions (integrated marketing, internal marketing, relationship marketing, and social marketing) on ​​the customer’s mental position in its dimensions (cognitive, emotional, and behavioral). The research problem was to know the extent of the impact of marketing quality management in the mental status of the customer. The sample consisted of managers in private banks in the city of Baghdad. (120) questionnaires were distributed, and the number of questionnaires returned and suitable for statistical analysis was (91) forms. The research is based on a set of basic hypotheses, including that marketing quality management affects the customer’s mental position. The problem of the study lies in the fact that many banks have begun to face some problems, including the inefficiency of marketing quality management, which leads to a decline in the mental position of the customer. Therefore, it has become necessary for marketing quality management to be carried out on studied scientific foundations. The study followed the descriptive analytical approach; the questionnaire was used to collect data, and the programs (SPSSV.28) were relied upon to analyze the data. The research reached several results, the most important of which is the existence of a link and influence between marketing quality management and the customer’s mental position.